La Chartreuse de Parme - Stendhal 1783-1842; Morand, Paul 1888-1976; Didier, Béatrice -1935 (Paris Gallimard, 1994)
'La Chartreuse de Parme' chronicles the adventures of the young Italian nobleman Fabrice del Dongo from his birth in 1798 to his death. Fabrice spends his early years in his family's castle on Lake Como, while most of the rest of the novel is set in a fictionalized Parma (both locations are in modern-day Italy).
Marie-Henri Beyle (1783-1842), better known by his pen name Stendhal was a 19th-century French writer. He is highly regarded for the acute analysis of his characters' psychology and considered one of the early and foremost practitioners of realism. A self-proclaimed egotist, he coined the same characteristic in his characters' "Beylism".
'La Chartreuse de Parme' is a novel by Stendhal published in 1839. Telling the story of an Italian nobleman in the Napoleonic era and later, it was admired by Balzac, Tolstoy, André Gide, di Lampedusa and Henry James. It was inspired by an inauthentic Italian account of the dissolute youth of Alessandro Farnese. The novel has been adapted for opera, film and television.
Keywords: 19th Century (1801-1900); Novel; France